2003
DOI: 10.2298/sarh0306232m
|View full text |Cite
|
Sign up to set email alerts
|

Advantageous usage combined spinal, epidural and general anesthesia versus general anesthesia in abdominal surgery

Abstract: Type and technique of anesthesia have an important effect on per operative surgical course. The aim of the study was prospective analyses of advantages of combined spinal, epidural and general anesthesia (CSEGA) versus general anesthesia (GA) in abdominal surgery according to: 1. operative course (haemodynamic stability of patients, quality of analgesia, undesirables effects), 2. postoperative course (quality of analgesia, unfavourable effects, temporary abode of patients in intensive care). Using prospective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 7 publications
1
2
0
Order By: Relevance
“…Other studies have demonstrated the advantages of the spinal anaesthetic technique, again reporting a decrease in local, inhaled and narcotic anaesthesia requirements. 23,24 Patients in the SA group in the present study showed statistically and clinically • Received for publication 4 September 2011 • Accepted subject to revision 8 October 2011…”
Section: Discussionsupporting
confidence: 54%
“…Other studies have demonstrated the advantages of the spinal anaesthetic technique, again reporting a decrease in local, inhaled and narcotic anaesthesia requirements. 23,24 Patients in the SA group in the present study showed statistically and clinically • Received for publication 4 September 2011 • Accepted subject to revision 8 October 2011…”
Section: Discussionsupporting
confidence: 54%
“…Visceral pain due to peritoneal traction during surgical manipulation even if still only pain without hemodynamic drawbacks sometimes necessitate sedation and even induction of general anesthesia. [5] A fact that surgical manipulation on abdominal contents, visceral ligaments, and peritoneum produces abdominal visceral pain that may be associated with sever vagal stimulation that would produce reflex bradycardia and hypotension. [28] Culebras et al [11] documented that intrathecal nalbuphine 0.8 mg provides good intraoperative and early postoperative analgesia without side effects.…”
Section: Discussionmentioning
confidence: 99%
“…[4] During spinal anesthesia, manipulation of the viscera and peritoneum produces dragging abdominal pain that sometimes necessitates induction of general anesthesia. [5] Pain management for oncology patient is important for early mobilization, tuning the immune system, and attenuation of the serious immune suppression mediated by the surgically stimulated network of neuro-immune-endocrine interactions. [6]…”
Section: Introductionmentioning
confidence: 99%